(untitled) (International Journal of Nursing Education, 2019)
Child birth is a natural biological process and therefore the pain associated with it also received as normal and natural. Both pharmacological and non-pharmacological methods are used to reduce the pain perception during labour. Midwife should work with mothers during the prenatal period to identify the personal coping strategies and encourage make efficient and effective use of these resources. The objective of the study is to assess the level of knowledge regarding selected natural pain relief methods during labour and is to associate the level of knowledge with selected demographic variables. A descriptive research design was used. Purpose sampling technique was used. Data was collected through semi structured knowledge questionnaire. Data was analysed by descriptive and inferential statistics. The finding reveals that 36% of the subjects had adequate knowledge, 48% of them had moderate knowledge and only family income and place of residence had significant association with knowledge